Dimension of Sentang (Azadirachta excelsa Jack) and Production of Soybean (Glycine max (L) Merril) in Agroforestry System DIMENSI POHON SENTANG (Azadirachta excelsa Jack) DAN PRODUKSI KEDELAI (Glycine max (L) Merril) DI DALAM SISTEM AGROFORESTRI - Suci Ratna Puri; Nurheni Wijayanto; Arum Sekar Wulandari (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2016)
System which integrating forestry and agriculture is known by agroforestry. Utilizing of unproductive land below the trees will be more optimum. Sentang (Azadirachta excelsa Jack) is one of the plants that can be used in agroforestry system. The aim of this research was to know the effect of agroforestry toward tree dimension and production of some soybean varieties. Research design that was used in this research is split plot design that consisted of 2 factors and three repetitions. Planting pattern as a main plot is a the first factor, consisted of planting pattern of agroforestry (S1) and monoculture (S0). The second factor that was a submain plot is some varieties of soybean which consisted of variety of Grobogan, Anjasmoro, Tanggamus, and Wilis.The results shows that accretion mean of tree height, stem and crown diameter of Sentang in agroforestry plot are bigger than in monocultural plot. Lateral root in monocultural plot is deeper than in agroforestry plot. The difference of plant growth in each planting pattern of agroforestry is affected by interaction among plant component. Utilizing of some soybean varieties in agroforestry of sentang one year old did not result significant production than in monoculture pattern. In this research, variety Tanggamus and Wilis on monoculturural plot has better growth and production than variety of Grobogan and Anjasmoro.Key words: agroforestry, tree dimension, sentang (Azadirachta excelsa Jack), soybean, varieties.